PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION YANG DIMEDIASI OLEH WORKPLACE INCIVILITY - Uswatun Chasanah; Dita Wahyu Saputra (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
The purpose of this study is to examine the effect of job satisfaction on turnover intention mediated by workplace incivility. Workplace incivility is uses as an intervening variable. This study uses a path analysis approach to determine the relationship between variables, namely, job satisfaction, workplace incivility and also turnover intention. The population in this study were coffee shop employees. The method of data collection is done by a survey through a questionnaire with a Likert scale measurement. The number of samples of 100 respondents using non-probability sampling with purposive sampling method. The validity test shows all valid variables and Cornbach Alpha reliability tests are all reliable. The results of the research questions have been proven correct. Job satisfaction is a positive effect on turnover intention which is mediated by workplace incivility. Kata kunci: Job Satisfaction, Workplace Incivility, Turnover Intention